Meningkatkan Hasil Belajar Passing Bawah Bola Voli melalui Model Pembelajaran Part Whole pada Siswa SMPN 3 Bolangitang - Suriyadi Datau; Muhammad Faisal Lutfi Amri (Departement of Mathematics Education, 2023)
The results of this study were based on or motivated by the technique of underhand passing in the learning of students at SMP Negeri 3 Bolangitang which were still not optimal or the application of good and correct movements, this was based on the results of observations that it turned out that there were still many students who got results below the KKM score. The output of this study is to identify and identify the effect of the Whole Part learning method on the ability to learn to pass under volleyball in students of SMP Negeri 3 Bolangitang. The research method used is classroom action research. Based on the results of the description of the percentage recapitulation of the initial data before being given action, it can be explained that the majority of students have not shown good learning outcomes, with a learning completeness percentage of 0% of students. As for the percentage in the Low category of 73.33% and 26.67% for the Enough category. For classical value acquisition in the initial observation. Based on the data in table 4, the following results were obtained: on the results of the initial observation assessment on the underhand serve in volleyball games, in the range of values 30-49 in the low category obtained an average score of 44.48 with a total of 11 students with a percentage of 73.33 % and in the range of values 50-69 in the Enough category, the average score is 53.57 with 4 students with a percentage of 26.67%. As for the overall value of the initial observation on the under serve in the volleyball game, a score of 46.90 is in the Low category. in the entire cycle I on the under serve in the volleyball game, in the range of 50-69 in the Fair category, the average score was 65.18 with 8 students with a percentage of 53.33% and in the range of 70-84 in the High category, the average value of 73.98 with a total of 7 students with a percentage of 46.67%. As for the overall value of the first cycle in the underhand serve in the volleyball game, a score of 69.29 was in the Enough category. in the entire cycle II on the under serve in the volleyball game, in the range of 70-84 the high category obtained an average score of 77.50 with a total of 10 students with a percentage of 66.67% and in the range of values 85-100 with the Very High category obtained an average score of 85.71 with a total of 5 students with a percentage of 33.33%. Whereas for the overall value of cycle II on the bottom serve in volleyball games, a score of 80.24 is in the High category. The results of this study were based on or motivated by the technique of underhand passing in the learning of students at SMP Negeri 3 Bolangitang which were still not optimal or the application of good and correct movements, this was based on the results of observations that it turned out that there were still many students who got results below the KKM score. The output of this study is to identify and identify the effect of the Whole Part learning method on the ability to learn to pass under volleyball in students of SMP Negeri 3 Bolangitang. The research method used is classroom action research. Based on the results of the description of the percentage recapitulation of the initial data before being given action, it can be explained that the majority of students have not shown good learning outcomes, with a learning completeness percentage of 0% of students. As for the percentage in the Low category of 73.33% and 26.67% for the Enough category. For classical value acquisition in the initial observation. Based on the data in table 4, the following results were obtained: on the results of the initial observation assessment on the underhand serve in volleyball games, in the range of values 30-49 in the low category obtained an average score of 44.48 with a total of 11 students with a percentage of 73.33 % and in the range of values 50-69 in the Enough category, the average score is 53.57 with 4 students with a percentage of 26.67%. As for the overall value of the initial observation on the under serve in the volleyball game, a score of 46.90 is in the Low category. in the entire cycle I on the under serve in the volleyball game, in the range of 50-69 in the Fair category, the average score was 65.18 with 8 students with a percentage of 53.33% and in the range of 70-84 in the High category, the average value of 73.98 with a total of 7 students with a percentage of 46.67%. As for the overall value of the first cycle in the underhand serve in the volleyball game, a score of 69.29 was in the Enough category. in the entire cycle II on the under serve in the volleyball game, in the range of 70-84 the high category obtained an average score of 77.50 with a total of 10 students with a percentage of 66.67% and in the range of values 85-100 with the Very High category obtained an average score of 85.71 with a total of 5 students with a percentage of 33.33%. Whereas for the overall value of cycle II on the bottom serve in volleyball games, a score of 80.24 is in the High category.